Comparison of the far-field aerodynamic wake development for three DrivAer model configurations using a cost-effective RANS simulation - Soares, Renan F.; Garry, Kevin P.; Holt, Jennifer C. (Society of Automotive Engineers (SAE), 2017)
The flow field and body aerodynamic loads on the DrivAer reference model have been extensively investigated since its introduction in 2012. However, there is a relative lack of information relating to the models wake development resulting from the different rear-body configurations, particularly in the far-field.Given current interest in the aerodynamic interaction between two or more vehicles, the results from a preliminary CFD study are presented to address the development of the wake from the Fastback, Notchback, and Estateback DrivAer configurations. The primary focus is on the differences in the far-field wake and simulations are assessed in the range up to three vehicle lengths downstream, at Reynolds and Mach numbers of 5.2×106 and 0.13, respectively.Wake development is modelled using the results from a Reynolds-Averaged Navier-Stokes (RANS) simulation within a computational mesh having nominally 1.0×107 cells. This approach was chosen to reflect a simple, cost-effective solution, using an industry-standard CFD solver. Each vehicle configuration has a smooth underbody, with exterior rear-view mirrors. The computational modelling includes a ground simulation set, and all simulations are for zero freestream yaw angle. A mesh sensitivity study was undertaken and the simulation validated against published experimental data for the body pressure distribution and aerodynamic drag.Critical assessment of the results highlights the benefits of focussed mesh refinement and specific numerical strategies for optimum performance of the CFD solver. Comparison of the far-field aerodynamic wake for the three model configurations exhibits significant differences in both extent and structure within the wake region up to three vehicle lengths downstream of the base. Total pressure loss coefficient is used as the primary aerodynamic parameter for analysis. The study is an element of a larger programme related to vehicle wake simulation and strategies are identified for possible wake modelling using simplified, computationally and experimentally efficient, shapes.